Combined cycle versus one thousand diesel power plants: pollutant emissions, ecological efficiency and economic analysis - Silveira, Jose Luz; de Carvalho, Joao Andrade; de Castro Villela, Iraides Aparecida (Elsevier B.V., 2007)
The increase in the use of natural gas in Brazil has stimulated public and private sectors to analyse the possibility of using combined cycle systems for generation of electrical energy. Gas turbine combined cycle power plants are becoming increasingly common due to their high efficiency, short lead times, and ability to meet environmental standards. Power is produced in a generator linked directly to the gas turbine. The gas turbine exhaust gases are sent to a heat recovery steam generator to produce superheated steam that can be used in a steam turbine to produce additional power. In this paper a comparative study between a 1000 MW combined cycle power plant and 1000 kW diesel power plant is presented. In first step, the energetic situation in Brazil, the needs of the electric sector modification and the needs of demand management and integrated means planning are clarified. In another step the characteristics of large and small thermoelectric power plants that use natural gas and diesel fuel, respectively, are presented. The ecological efficiency levels of each type of power plant is considered in the discussion, presenting the emissions of particulate material, sulphur dioxide (SO2), carbon dioxide (CO2) and nitrogen oxides (NOx). (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: natural gas; diesel oil; ecological efficiency